Circulating tRNA-derived small RNAs (tsRNAs) signature for the diagnosis and prognosis of breast cancer - Jingyi Wang; Ge Ma; Han Ge; Xu Han; Xinrui Mao; Xinyang Wang; Jordee Selvamanee Veeramootoo; Tiansong Xia; Xiaoan Liu; Shui Wang (npj Breast Cancer, 2021)
Abstract Liquid biopsy is noninvasive and convenient to detect cancer-derived materials in blood or other body fluids. The aim of this study was to identify tRNA-derived small RNAs (tsRNAs) in plasma that could distinguish patients with breast cancer (BC) from healthy controls. Basing on high-throughput sequencing, 15 significantly upregulated tsRNAs were selected and assessed in cell supernatants and cell lines. 6 tsRNAs were identified and verified in a large cohort of 120 patients with BC and 112 healthy controls. tRF-Arg-CCT-017, tRF-Gly-CCC-001, and tiRNA-Phe-GAA-003 could serve as novel diagnostic biomarkers. Meanwhile, tRF-Arg-CCT-017 and tiRNA-Phe-GAA-003 could also act as prognostic biomarkers. Target genes of these tsRNAs were related to the development of cancers. These results suggested that specific tsRNAs in plasma might serve as diagnostic and prognostic biomarkers of BC.